2009
DOI: 10.1166/jnn.2009.441
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Multi-Walled Carbon Nanotubes

Abstract: The magnetic properties of multiwall carbon nanotubes (MWCNTs) grown by microwave plasma enhanced chemical vapor deposition (MPECVD) were studied by electron paramagnetic resonance and magnetization measurements. The ferromagnetic characters of virgin grown MWCNTs are mainly attributed to the catalyst nanoparticles embedded on the tips. After acid etching for purification, the trace of magnetic resonance prominently distributed from the remnant of catalyst nanoparticles within the lower sectional parts of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The magnetic properties of nanotubes and their response in the presence of an external magnetic field are reported by Lopez et al [5,6]. Chang and Lue [7] considered multiwall carbon nanotubes (MWCNTs) and investigated their magnetic properties by electron paramagnetic resonance and magnetization measurements. Reddy et al [8] considered metal-filled multi-walled nanotubes and studied their magnetic properties by using vibrating sample magnetometry.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic properties of nanotubes and their response in the presence of an external magnetic field are reported by Lopez et al [5,6]. Chang and Lue [7] considered multiwall carbon nanotubes (MWCNTs) and investigated their magnetic properties by electron paramagnetic resonance and magnetization measurements. Reddy et al [8] considered metal-filled multi-walled nanotubes and studied their magnetic properties by using vibrating sample magnetometry.…”
Section: Introductionmentioning
confidence: 99%
“…MWCNTs have been the subject of numerous reports in recent years. Likodimos et al studied the magnetic properties of MWCNTs, [7] discovering an increase in diamagnetic susceptibility at low temperatures, and it is confirmed that there is an optical Aharonov-Bohm (AB) effect in the quantum ring of MWCNTs. Chang et al presented a variety of magnetic resonance spectra of MWCNTs, and attributed the magnetism of carbon nanotubes to coupling between the free spins of dangling bonds, which also results in weak ferromagnetism coupling.…”
Section: Introductionmentioning
confidence: 96%
“…fuel cells and batteries), aeronautic and astronautic technology, automobile, and many other modern industries. 17 In addition, it is shown that the vibration investigation of bonded double-plate system, which can be modeled as composite structures, is important for both theoretical and practical reasons 8,9 such as nano-optomechanical systems (NOMS).…”
Section: Introductionmentioning
confidence: 99%
“…18 Magnetic field effects on the vibration of the graphene sheets are important for exciting potential applications in nanotechnology such as in NEMS, MEMS, nanosensors, spintronics, and nanocomposites. 17 In recent years, a large amount of research works have been carried out on the behavior of graphene in a magnetic field. Murmu et al 19 studied the effect of an in-plane magnetic field on the transverse vibration of a magnetically sensitive SLGS.…”
Section: Introductionmentioning
confidence: 99%